(untitled) (Revista de Administração, 2016)
This study aimed to identify satisfaction antecedents presented by sugar cane producers with the associations they belong to. It was developed a model composed of seven dimensions which were grouped into two types: individual aspects (economic, networking and honor) and collective aspects (perception of services, representation, trust and relevance of the association). It was performed one quantitative and descriptive study, conducted through questionnaires applied directly to producers. 550 questionnaires were completed and 411 of these were valid. For the data analysis, correlation and multiple linear regression between the variables were used. The results showed that all seven variables were positively correlated with satisfaction, however, only five of them comprised the final model after multiple linear regression: perception of services offered, representation, trust, economical aspect and honor. Surprisingly, the results also showed that collective aspects affected more the satisfaction than individual aspects.